IMPLEMENTASI MEDIA PEMBELAJARAN DALAM PENDIDIKAN AGAMA ISLAM - Hasibuan, Nasruddin (IAIN Padangsidimpuan, 2016)
This paper aims to determine how the implementation of instructional media in Islamic education. The method of writing using library research methods. From the discussion, it can be concluded that the media is a kind of learning aids and learning, both in class and outside of class. The existence of learning media is very helpful in achieving educational goals despite many shortcomings yanng therein. It is expected that teachers' creativity in choosing which media is more suitable to be applied in the classroom. In this case, which must be considered is the material that will be presented, and a means of pre-class situation means.